2014
DOI: 10.1148/radiol.14131819
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Urinary Obstruction: Evaluation of Dynamic Contrast-enhanced MR Urography for Measurement of Split Renal Function

Abstract: ).q RSNA, 2014 Purpose:To evaluate if measurement of split renal function (SRF) with dynamic contrast material-enhanced (DCE) magnetic resonance (MR) urography is equivalent to that with renal scintigraphy (RS) in patients suspected of having chronic urinary obstruction. Materials and Methods:The study protocol was approved by the institutional ethics committee of the coordinating center on behalf of all participating centers. Informed consent was obtained from all adult patients or both parents of children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 33 publications
2
22
0
1
Order By: Relevance
“…Chronic urinary obstruction can show split renal function (SRF), which is defined as a quantity associated with the function of a single kidney. In patients with moderately hydronephrotic kidneys, the accuracy of DCE‐MRI urography for SRF measurements can be equivalent to that of renal scintigraphy (RS) . Inflammatory renal conditions (such as pyelonephritis and abscess) also decrease ADC values because of edema, increased cellularity, and fibrosis.…”
Section: Applications Of Renal Fmrimentioning
confidence: 99%
“…Chronic urinary obstruction can show split renal function (SRF), which is defined as a quantity associated with the function of a single kidney. In patients with moderately hydronephrotic kidneys, the accuracy of DCE‐MRI urography for SRF measurements can be equivalent to that of renal scintigraphy (RS) . Inflammatory renal conditions (such as pyelonephritis and abscess) also decrease ADC values because of edema, increased cellularity, and fibrosis.…”
Section: Applications Of Renal Fmrimentioning
confidence: 99%
“…SRF can be estimated with renal scintigraphy performed with various radionuclides, including 99m Tc-labeled dimercaptosuccinic acid ( 99m Tc-DMSA), 99m Tc-labeled mercaptoacetyltriglycine ( 99m Tc-MAG3), and 99m Tc-labeled diethylenetriaminepentaacetate ( 99m Tc-DTPA) [1–4]. Other noninvasive modalities and procedures for calculating SRF include CT angiography [3, 5], dynamic contrast-enhanced MR urography [6], and DWI [7]. Among these, 99m Tc-DMSA renal scintigraphy has been considered the most sensitive method for proving the existence of parenchymal damage due to acute or chronic pyelonephritis and acquiring data on differential kidney function [4, 8, 9].…”
mentioning
confidence: 99%
“…However, even when isotope renogram results are compromised by reduced radiotracer uptake in the affected kidney, dMRI has proved to be a very good modality to differentiate between an obstructed dilated and a non-obstructed upper urinary tract. [19] However, a large multi-center study published in 2014 by Claudon et al [20] showed that dMRI was equivalent to renal scintigraphy in moderately dilated kidneys; but dMRI underestimated split renal function by 4% in severely dilated kidneys, making substitution of renal scintigraphy questionable. The advantages of MRI over other radiological techniques are exquisite soft tissue characterization, capability of direct multiplanar and three dimensional reformatting images, and lack of ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%